Effects of various supplemental starch and protein levels on ruminal fermentation and liquid passage of beef steers fed tallgrass-prairie hay - R.C. Cochran; E.S. Vanzant; K. C. Olson; Timothy J. Jones; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1997)
The effect of supplements containing various proportions of degradable intake protein (DIP) and starch on ruminal digestion characteristics of forage-fed beef steers was evaluated. Fluid passage rates, ruminal ammonia (N H), 3 and total volatile fatty acid (VFA) concentrations increased as the amount of supplemental DIP increased. Starch infused at .3% of BW increased molar proportion s of propionate and butyrate and decreased acetate, compared to feeding DIP alone. However, proportions of branched-chain VFA increased with DIP at all levels of starch infusion. Total digestible organic matter intake (TDOMI) was increased with each addition of DIP; however, infusing starch within a DIP level decreased TDOMI. Providing supplemental DIP is more important for improving the use of low-quality, tallgrass-prairie hay than is ruminally available starch.
Keywords: Cattlemen& #x27; s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Beef steers; Protein; Starch; Supplements; Ruminal fermentation